Dental RECUR Randomized Trial to Prevent Caries Recurrence in Children. (February 2020) - Pine, C.M.; Adair, P.M.; Burnside, G.; Brennan, L.; Sutton, L.; Edwards, R.T.; Ezeofor, V.; Albadri, S.; Curnow, M.M.; Deery, C.; Hosey, M.T.; Willis-Lake, J.; et al.
The purpose of this study was to determine the efficacy of a dental nurse–delivered intervention—the Dental RECUR Brief Negotiated Interview for Oral Health (DR-BNI)—in reducing the recurrence of dental caries in children who have a primary tooth extracted. It was based on a 2-arm multicenter randomized controlled trial with blinded outcome assessment. Participants were 5- to 7-y-old children ( n = 241) scheduled to have primary teeth extracted in 12 UK centers. Test intervention parents ( n = 119) received DR-BNI led by trained dental nurses. DR-BNI is a 30-min structured conversation informed by motivational interviewing with a forward focus to prevent future caries. Preventive goals are agreed, and a review appointment is made with child's general dental practitioner, who is advised to treat the child as being at high caries risk. The control intervention ( n = 122) was a parent-nurse conversation about child's future tooth eruption, with advice given to visit a general dental practitioner as usual. At baseline, the DR-BNI group's mean dmft was 6.8, and the control group's was 6.3. A median of 5 teeth were extracted, mainly under general anesthesia. Final dental assessments were conducted by a single examiner visiting 189 schools 2 y after intervention; 193 (80%) of 241 children were examined. In the control group, 62% developed new caries in teeth that were caries-free or unerupted at baseline, as compared with 44% in the test group, a significant reduction ( P = 0.021). The odds of new caries experience occurring were reduced by 51% in the DR-BNI group as compared with control. There was a 29% decrease in the relative risk of new caries experience in the DR-BNI group as compared with control. This single low-cost, low-intensity intervention was successful in significantly reducing the risk of recurrence of dental caries in children. This trial has implications for changing pediatric dental practice internationally. Training in and implementation of a motivational interviewing–informed brief intervention provides opportunities for dental nurses to facilitate behavior change improving the oral health of children at high caries risk (ISRCTN 24958829).